2008
DOI: 10.1002/bjs.6240
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of 21 178 patients undergoing open or endovascular repair of abdominal aortic aneurysm

Abstract: The endovascular repair of AAA offers a clear benefit in terms of reduction in postoperative adverse events and 30-day mortality. In the longer term, it is also associated with a reduction in aneurysm-related mortality, but not in all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 99 publications
3
101
0
2
Order By: Relevance
“…19 Stather et al undertook a large metaanalysis and reported that EVAR and open repair were equivalent with respect to all-cause mortality at 2 years, 4 years, and longer periods after surgery and with respect to late AAArelated mortality. 22 In the present study, the cumulative survival rate was lower in the EVAR group compared with the OS group, which can be explained by the older age of the EVAR group.…”
Section: Discussionmentioning
confidence: 99%
“…19 Stather et al undertook a large metaanalysis and reported that EVAR and open repair were equivalent with respect to all-cause mortality at 2 years, 4 years, and longer periods after surgery and with respect to late AAArelated mortality. 22 In the present study, the cumulative survival rate was lower in the EVAR group compared with the OS group, which can be explained by the older age of the EVAR group.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Most series report principally cardiovascular and respiratory complications. 10 All patients seen in pre-operative assessment clinic are warned that the procedure carries a 20% major morbidity rate and a 5% mortality rate. The majority of complications in this study were cardiovascular (nine cardiac events, three haemorrhages) and all 30-day mortalities were aneurysm-related (three myocardial infarctions, one multi-organ failure).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of over 21,000 cases concluded that EVAR is a safe and effective alternative in high-risk patients as it reduces short-term complications and aneurysm related deaths when compared to open repair. [10][11][12] EVAR is more cost effective in the short term. The costs per patient of the primary procedure and hospitalisation for the EVAR 1 trial were £10,818 and £9,204 for EVAR and open repair, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Compared with previous prosthetic graft replacement techniques, endovascular aneurysm repair (EVAR) has been shown to significantly reduce operative mortality rate, the frequency of perioperative complications, perioperative blood loss, required blood transfusion volumes, and duration of hospital stay, predominantly because of substantially lower degree of invasiveness of EVAR. 5,6) However, EVAR has a number of limitations including a high re-intervention rate and an association with contrast medium-induced renal dysfunction. The prevalence of preoperative renal dysfunction in patients with AAA is reportedly approximately 10%, 7) with management strategies for the preservation of renal function considered clinically important.…”
Section: Introductionmentioning
confidence: 99%